2020
DOI: 10.3390/land9080237
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential and Contribution of UNESCO Biosphere Reserves for Landscape Governance and Management in Africa

Abstract: United Nations Educational Scientific and Cultural Organization (UNESCO) Biosphere Reserves strive for a harmonious interaction between humans and nature. As landscapes provide suitable units to mutually address matters of conservation and sustainable development, this study aims to explore the potential and realized contribution of biosphere reserves for landscape governance and management. We emphasize the role of stakeholder participation and cooperation as an overarching condition for integrated landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The paper found that, due to the disputed nature of informal settlements, local residents are more predisposed to interact with researchers than government agents. In co-identifying and designing solutions, the neutral role of the researchers enhances trust and supports the leveraging of efforts across sectors (Hedden-Dunkhorst and Schmitt [10], Kusters et al [6]).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The paper found that, due to the disputed nature of informal settlements, local residents are more predisposed to interact with researchers than government agents. In co-identifying and designing solutions, the neutral role of the researchers enhances trust and supports the leveraging of efforts across sectors (Hedden-Dunkhorst and Schmitt [10], Kusters et al [6]).…”
mentioning
confidence: 99%
“…BE TRANSPARENT AND OPEN: Given the diversity of interests and values of landscape actors, transparency and openness should be encouraged in all stakeholder interactions, and across all decision-making processes and land governance structures. Hedden-Dunkhorst and Schmitt [10] show the importance of transparency to promote realistic expectations on livelihood improvements in biosphere reserve management. Transparency helps build trust among stakeholders and makes them comfortable about the values they hold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ˆIntegrar las necesidades y opiniones de las comunidades locales dentro del grupo de agentes involucrados en el diseño de las estrategias. De hecho, está demostrado que la consecución de objetivos de conservación es más probable cuando se fomentan los beneficios socioeconómicos a través de la sostenibilidad cultural y la integración de las comunidades locales (Oldekop et al 2016;Hedden-Dunkhorst & Schmitt, 2020).…”
Section: Introduccionunclassified
“…The details of the interviewers are shown in the Table 4. Interview questions were developed through the participatory observation of local communities and a literature review [51]. To test the questions, we conducted semistructured interviews with two experts from MHBR (summer 2018) and one expert from KatBR (spring 2018).…”
mentioning
confidence: 99%